Dialectología hispánica = The Routledge handbook of Spanish dialectology - Moreno Fernández, Francisco; Caravedo, Rocío (Routledge Spanish language handbooks, 2023)
"Dialectología hispánica / The Routledge Handbook of Spanish Dialectology is a choral work that provides the latest research on the current varieties of the Spanish language in all its geographies, collating expertise from a wealth of leading scholars in the subject. This volume is comprised of 49 chapters, distributed in four sections, which offer up-to-date information on the dialectal reality of Spanish and reflect the knowledge available on the language and its varieties. This comprehensive and innovative book explores the way in which various linguistic specialities are interested in dialectal variation, from history to computer science, including phonetics, grammar and lexicography, among other disciplines. Displaying a commitment to a multidimensional view of dialectal spaces, this handbook associates geolinguistic variation not only with history and sociology, but also with ethnic, stylistic and cognitive factors. Presenting an in-depth exploration of Spanish dialectology in all its expressions across the Spanish-speaking space, this resource is ideal for all researchers interested in Spanish linguistics, linguistic variation and language contact, as well as for undergraduate and graduate students"--